Pengaruh Campuran Limbah Anorganik (Plastik) Sebagai Pengganti Semen Terhadap Kuat Tekan Paving Block - Siti Nurul Hijah; Mohammad Hamsyuni; Prita Dewi Basoeki; Isdaryanto Iskandar (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
The increased production of waste that is hard to degrade is inorganic waste, so it takes effort to reduce it into a useful product. One of the alternatives, inorganic waste recycling is becoming one of the mixture ingredients of paving blocks. This research aimed to determine the best composition of mixture ingredients towards the compressive strength of paving blocks with plastic waste as a substitute for cement. Research methods with experimental testing in the laboratory using paving blocks mixed with plastic waste as a substitute for cement. Plastic waste used is cleaned first and dried, chopped into smaller pieces afterward, and heated inside a cauldron until melted and ready to be mixed with sand. The composition used is 80% plastic: 20% sand, 70% plastic: 30% sand, 60% plastic: 40% sand, and 50% plastic: 50% sand. The result of the compressive strength test of paving block composition affected by a proper mixture of plastic waste as a substitute of cement towards compressive strength of paving block is type LDPE with a variation of 50%: 50%, with average compressive strength of 8,5 MPa with category D of paving block quality that good to be used for park and another usage. For the absorption capacity test of the paving blocks that absorb most of the water is located in the ratio of 50% plastic: 50% sand with 1,30% satisfy SNI requirement 03-0691-1996 entering grade A with average water absorption of 3%.